Revisiting periurban water (in)security in South Asia - Narain, Vishal; Vij, Sumit (International Journal of Water Governance, 2023)
The Sixth Assessment Report (AR6) of the Intergovernmental Panel on Climate Change (IPCC) has identified periurban development as one of the major drivers of climate risk on vulnerable communities. At the same time, ‘grand challenges’ such as the Covid pandemic and urban–rural contestations create a new imperative for renewed attention to issues of periurban water insecurity by drawing attention to living conditions in periurban spaces where people live in crowded and often informal settlements with inadequate access to safe water. Understanding periurban water insecurity requires paying attention to the dynamic processes of change characterising periurban spaces that make access to water in periurban spaces uncertain and fluctuating. Rather than focus on quantitative indicators of periurban water insecurity or assume that reclassification of jurisdiction status will improve periurban water security, action research with robust partnerships across academia, government and civil society organisations should inform approaches to improve water governance in periurban spaces.